Post‐exposure prophylaxis for HIV infection in sexual assault victims. Issue 1 (11th October 2019) - Inciarte, A; Leal, L; Masfarre, L; Gonzalez, E; Diaz‐Brito, V; Lucero, C; Garcia‐Pindado, J; León, A; García, F; ,
Abstract : Objectives: Sexual assault (SA) is recognized as a public health problem of epidemic proportions. Guidelines recommend the administration of post‐exposure prophylaxis (PEP) after an SA. However, few data are available about the feasibility of this strategy, and this study was conducted to assess this. Methods: We conducted a retrospective, longitudinal, observational study in SA victims attending the Hospital Clinic in Barcelona from 2006 to 2015. A total of 1695 SA victims attended the emergency room (ER), of whom 883 met the PEP criteria. Five follow‐up visits were scheduled at days 1, 10, 28, 90 and 180 in the out‐patient clinic. The primary endpoint was PEP completion rate at day 28. Secondary endpoints were loss to follow‐up, treatment discontinuation, occurrence of adverse events (AEs) and rate of seroconversion. Results: The median age of participants was 25 years [interquartile range (IQR) 21–33 years] and 93% were female. The median interval between exposure and presentation at the ER was 13 h (IQR 6–24 h). The level of risk was appreciable in 47% ( n  = 466) of individuals. Of 883 patients receiving PEP, 631 lived in Catalonia. In this group, the PEP completion rate at day 28 was 29% ( n  = 183). The follow‐up rate was 63% ( n  = 400) and 38% ( n  =   241) at days 1 and 28, respectively. Treatment discontinuation was present in 58 (15%) of 400 patients who attended at least the day 1 visit, the main reason being AEs ( n  = 35; 60%). AEs were reported in 226 (56%) patients, and were mainly gastrointestinal ( n  = 196; 49%). Only 211 (33%) patients returned for HIV testing at day 90. A single seroconversion was observed in a men who have sex with men (MSM) patient at day 120. Conclusions: Follow‐up and compliance rates in SA victims were poor. In addition, > 50% of the patients experienced AEs, which were the main reason for PEP interruption. Strategies to increase follow‐up testing and new better tolerated drug regimens must be investigated to address these issues.